Update breast cancer 2018 (Part 1) - primary breast cancer and biomarkers - Ţăran, Florin-Andrei; Schneeweiss, Andreas; Wallwiener, Markus; Schütz, Florian (Geburtshilfe und Frauenheilkunde, 2018)
This summary provides an overview of how new therapies or new aspects of established therapies relate to the latest findings. Neoadjuvant therapy, local therapy, new aspects of systemic therapy, and prognostic and predictive factors are presented. In the neoadjuvant setting, the association between pathological complete response (pCR) and prognosis is still of interest as is the identification of new molecular predictors for new therapies such as CDK4/6 inhibitors. As regards surgical treatment, the target is still to reduce the aggressiveness of surgery. To achieve this, a better understanding particularly of ductal carcinoma in situ is required. With regard to systemic therapy, more data on the best combinations and therapy sequences for existing therapies is available. Finally, the use of prognostic and predictive factors may help to avoid overtreatment and ensure that patients only receive therapies which have been shown to be effective for their specific condition and have fewer side effects.